Enterococcal bacteremia in children with malignancy or after hematopoietic stem cell transplantation: real-world multicenter data from a nationwide survey in Poland (2014–2021) - Tomasz Ociepa; Aleksandra Królak; Hubert Kluk; Krzysztof Czyżewski; Kamila Jaremek; Oliwia Grochowska; Patrycja Zalas-Więcek; Katarzyna Derwich; Jacek Wachowiak; Agnieszka Mizia-Malarz; Weronika Stolpa; Karolina Baranowska; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Probing salty waters: re-assessment of the early stages of calcium carbonate formation in seawater - Anthea I. Arns; David Evans; Ralf Schiebel; Stephan E. Wolf; Anne Jantschke; Maximilian Hansen; Jan Leitner; Hubert Vonhof; Gerald H. Haug (Geochimica et Cosmochimica Acta, 2026)

Investigation of Dalmatian population ancestry in golden jackals in nearby regions - Tamara Kovačič; Marjeta Konec; Barbara Boljte; Tihomir Florijančić; Maja Jan; Hubert Potočnik; Alexandros A. Karamanlidis; Josip Kusak; Davide Righetti; Tamara Schenekar; Tomaž Skrbinšek; Nikica Šprem; et al. (Mammal Research, 2026)
Although the golden jackal ( Canis aureus ) has been present in south-eastern Europe for over 500 years, its northern and western range expansion appears recent. Genetic analyses indicate that a contact zone between the previously identified Dalmatian and Pannonian populations has developed in south-western Slovenia and north-eastern Italy. To better understand the spatial extent of the contact zone, we analysed 27 new genetic samples from western Croatia ( n = 13), north-eastern Italy ( n = 6), south-eastern Austria ( n = 3), and northern Greece ( n = 5), which we combined with existing Dalmatian and Pannonian reference profiles ( n = 46). Individuals from Austria, Greece, and most jackals from Croatia (the island of Krk and Plitvice National Park) and Italy were assigned to the Pannonian population. One jackal from Italy and one from Croatia (the island of Dugi Otok) showed admixed Pannonian-Dalmatian ancestry, but none was assigned to the Dalmatian population. Although the small sample size warrants cautious interpretation, our results indicate that the Dalmatian population may have a restricted distribution, in contrast to the widespread and expanding Pannonian population. Future analyses with known reference populations are necessary to help clarify jackal gene flow along the southern Adriatic coast, including the coastal islands.

Cultures of stored-product mite Tyrophagus putrescentiae experimentally infected with Cardinium and Wolbachia presented reduced fitness - Jan Hubert; Eliza Glowska-Patyniak; Stano Pekar (Journal of Stored Products Research, 2025)

Chemical risk analysis competence in the Nordics is at stake - Åke Bergman; Hrönn Jörundsdóttir; Lisbeth E. Knudsen; Matti Viluksela; Jan Alexander; Åse Krøkje; Kimmo Peltonen; Jaana Rysä; Anette Schnipper; Per Sporrong; Ingrid Ericson Jogsten; Halldór P. Halldórsson; et al. (Environmental Science and Pollution Research, 2025)
Toxicology-related experts are on a daily basis working with the safety assessment of chemicals for human health and the environment, providing knowledge applied for management and regulation of chemicals. The field of toxicology is undergoing continuous transition away from traditional safety evaluation studies in experimental animals to application of new approach methodologies (NAMs), the use of omics-related technologies, and concepts like next-generation risk assessment. This requires expertise in the new technologies but does not dismiss the need of knowledge for interpretation of in vivo studies and full understanding of chemical exposure data. A survey was initiated in 2022 in the Nordic countries to assess current and future needs for competences in risk analysis. In total, 40 replies were received from Denmark, Finland, Norway and Sweden, while an expert assessment was performed in Iceland. The responses primarily (87.5%) came from national authorities, research institutes, industry/business, and consultants, less from the hospital system, NGOs, and others. The survey shows obvious difficulties in finding competent and trained personnel in all areas in risk analysis. Since the individual Nordic countries lack critical mass, a Nordic initiative for training and education is recommended to counteract loss of competences within chemical risk analysis in the future.

Secondary metabolites and their impact on symbiotic interactions in the ambrosia fungus Geosmithia eupagioceri - Miroslav Kolařík; Eva Stodůlková; Soňa Kajzrová; Jaroslav Semerád; Jan Hubert; Marek Kuzma; Miroslav Šulc; Ivana Císařová; Andrej Jašica; Jan-Peer Wennrich; Jiří Hulcr; Miroslav Flieger (Fungal Ecology, 2025)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Genotype by year interaction for selected traits in sweet maize (Zea maize L.) hybrids using AMMI model - Jan Bocianowski; Hubert Waligóra; Leszek Majchrzak (Euphytica, 2024)
This study investigated genotype × environment interactions for the stability of expression of four productivity traits (cobs yield, cobs I class trade share, lend of cobs and fulfilment of cobs) of sweet maize hybrids ( Zea mays L.). The additive main effects and multiplicative interaction (AMMI) model was employed to assess genotype × environment interaction. AMMI stability value was used to evaluate both stability and genotype. The genotype selection index was calculated for each hybrid, incorporating both the average trait value and the stability index. Ten sweet maize hybrids were evaluated: Golda, GSS 1453, GSS 3071, GSS 5829, GSS 8529, Overland, Noa, Shinerock, Sindon, and Tessa. Trials were ran conducted over four vegetative seasons at a single location in the Wielkopolska region using replicated field experiments. The AMMI model revealed significant genotypic and environmental effects for all analyzed traits. Based on their superior stability and favorable average trait values, both the Golda cultivar and the GSS 3071 hybrid are recommended for further breeding program inclusion.

Mixta mediterraneensis as a novel and abundant gut symbiont of the allergen-producing domestic mite Blomia tropicalis - Tomas Erban; Bruno Sopko; Pavel B. Klimov; Jan Hubert (Experimental and Applied Acarology, 2024)
Blomia tropicalis is an allergen-producing mite in the human environment in tropical regions. The microbiome of B. tropicalis was described using the barcode sequencing region of V4 16S rDNA and genome assemblage. Mixta mediterraneensis , previously isolated from human skin swabs, was identified as a B. tropicalis gut symbiont based on genome assembly. The microbiome contains two bacteria, Staphylococcus and M. mediterraneensis . The number of M. mediterraneensis 16S DNA copies was 10 6 per mite and 10 9 per feces in the rearing chamber based on qPCR quantification. The profile of this bacterium reached 50% of reads in the mite gut and feces. Genomic analyses revealed that the bacterium has several metabolic pathways that suggest metabolic cooperation with the mite host in vitamin and amino acid synthesis, nitrogen recycling, and antimicrobial defense. Lysozyme is present in the symbiotic bacterium but absent in the mite. The B. tropicalis microbiome contained Staphylococcus , which accelerates mite population growth. Mites can digest Staphylococcus by using specific enzymes with hydrolytic functions against bacterial cell walls (chitinases and cathepsin D), leading to endocytosis of bacteria and their degradation in lysosomes and phagosomes. Gene expression analysis of B. tropicalis indicated that phagocytosis was mediated by the PI3-kinase/Akt pathway interacting with the invasins produced by M. mediterraneensis . Moreover, the symbiont had metabolic pathways that allowed it to recycle the mite metabolic waste product guanine, known as a mite attractant. The mite host symbiont enhances mite aggregation in the feces, and the fecal–oral transmission route is excepted.

Regulatory safety assessment of nanoparticles for the food chain in Europe - Reinhilde Schoonjans; Jacqueline Castenmiller; Qasim Chaudhry; Francesco Cubadda; Takis Daskaleros; Roland Franz; David Gott; Jan Mast; Alicja Mortensen; Agnes G. Oomen; Hubert Rauscher; Stefan Weigel; et al. (Trends in Food Science & Technology, 2023)

Population growth and respiration in the dust mite Dermatophagoides farinae under different temperature and humidity regimes - Tereza Vackova; Stano Pekar; Pavel B. Klimov; Jan Hubert (Experimental and Applied Acarology, 2023)

Sharing a bed with mites: preferences of the house dust mite Dermatophagoides farinae in a temperature gradient - Tereza Vackova; Stano Pekar; Pavel B. Klimov; Jan Hubert (Experimental and Applied Acarology, 2021)

Whole genomic sequencing and sex-dependent abundance estimation of Cardinium sp., a common and hyperabundant bacterial endosymbiont of the American house dust mite, Dermatophagoides farinae - Tomas Erban; Pavel Klimov; Vit Molva; Jan Hubert (Experimental and Applied Acarology, 2020)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Detection of tau-fluvalinate resistance in the mite Varroa destructor based on the comparison of vial test and PCR–RFLP of kdr mutation in sodium channel gene - Jitka Stara; Stano Pekar; Marta Nesvorna; Tomas Erban; Hana Vinsova; Jan Kopecky; Ivo Doskocil; Martin Kamler; Jan Hubert (Experimental and Applied Acarology, 2019)

Structural and functional mapping of geosigmeta in Atlantic coastal marshes (France) using a satellite time series - Sébastien Rapinel; Pauline Dusseux; Jan-Bernard Bouzillé; Anne Bonis; Arnault Lalanne; Laurence Hubert-Moy (Plant Biosystems, 2018)

Investigating species boundaries using DNA and morphology in the mite Tyrophagus curvipenis (Acari: Acaridae), an emerging invasive pest, with a molecular phylogeny of the genus Tyrophagus - Pamela Murillo; Pavel Klimov; Jan Hubert; Barry OConnor (Experimental and Applied Acarology, 2018)

Species-rich grassland can persist under nitrogen-rich but phosphorus-limited conditions - Han F. van Dobben; G. W. Wieger Wamelink; Pieter A. Slim; Jan Kamiński; Hubert Piórkowski (Plant and Soil, 2017)

Detection and localization of Solitalea-like and Cardinium bacteria in three Acarus siro populations (Astigmata: Acaridae) - Jan Hubert; Jan Kopecky; Marta Nesvorna; M. Alejandra Perotti; Tomas Erban (Experimental and Applied Acarology, 2016)

Comparison of tau-fluvalinate, acrinathrin, and amitraz effects on susceptible and resistant populations of Varroa destructor in a vial test - Martin Kamler; Marta Nesvorna; Jitka Stara; Tomas Erban; Jan Hubert (Experimental and Applied Acarology, 2016)

Prevalence of pathogenic bacteria in Ixodes ricinus ticks in Central Bohemia - Radek Klubal; Jan Kopecky; Marta Nesvorna; Olivier A. E. Sparagano; Jana Thomayerova; Jan Hubert (Experimental and Applied Acarology, 2016)

Influence of point estimates and study power of bioequivalence studies on establishing bioequivalence between generics by adjusted indirect comparisons - Luther Gwaza; John Gordon; Henrike Potthast; Jan Welink; Hubert Leufkens; Matthias Stahl; Alfredo García-Arieta (European Journal of Clinical Pharmacology, 2015)

Upscaling Nitrogen Removal Capacity from Local Hotspots to Low Stream Orders’ Drainage Basins - Gilles Pinay; Stefan Peiffer; Jean-Raynald De Dreuzy; Stefan Krause; David M. Hannah; Jan H. Fleckenstein; Mathieu Sebilo; Kevin Bishop; Laurence Hubert-Moy (Ecosystems, 2015)

Stored product mites (Acari: Astigmata) infesting food in various types of packaging - Jan Hubert; Marta Nesvorna; Vlado Volek (Experimental and Applied Acarology, 2015)

Two-dimensional gel proteomic analysis of Dermatophagoides farinae feces - Tomas Erban; Jan Hubert (Experimental and Applied Acarology, 2015)

Bartonella-like bacteria carried by domestic mite species - Jan Kopecký; Marta Nesvorná; Jan Hubert (Experimental and Applied Acarology, 2014)

Growth-suppressive effect of the α-amylase inhibitor of Triticum aestivum on stored-product mites varies by the species and type of diet - Jan Hubert; Marta Nesvorna; Tomas Erban (Experimental and Applied Acarology, 2014)

The effect of stored barley cultivars, temperature and humidity on population increase of Acarus siro, Lepidoglyphus destructor and Tyrophagus putrescentiae - Jan Hubert; Stano Pekár; Radek Aulický; Marta Nesvorná; Václav Stejskal (Experimental and Applied Acarology, 2013)

Computational model for estimating the short- and long-term cardiac response to arteriovenous fistula creation for hemodialysis - Wilco Kroon; Marielle Bosboom; Wouter Huberts; Jan Tordoir; Frans van de Vosse (Medical & Biological Engineering & Computing, 2012)

The efficacy of four avermectins on the synanthropic mite Lepidoglyphus destructor under laboratory conditions - Tomas Erban; Jakub Rybansky; Jan Hubert (Experimental and Applied Acarology, 2012)

A 40-year accumulation dataset for Adelie Land, Antarctica and its application for model validation - Cécile Agosta; Vincent Favier; Christophe Genthon; Hubert Gallée; Gerhard Krinner; Jan T. M. Lenaerts; Michiel R. van den Broeke (Climate Dynamics, 2012)

Emerging risk of infestation and contamination of dried fruits by mites in the Czech Republic - Jan Hubert; Tomas Erban; Marta Nesvorna; Vaclav Stejskal (Food Additives & Contaminants: Part A, 2011)

The toxicity of selected acaricides against five stored product mites under laboratory assay - Jitka Stará; Marta Nesvorná; Jan Hubert (Journal of Pest Science, 2011)

The effect of chitin metabolic effectors on the population increase of stored product mites - Jitka Stara; Tomas Erban; Jan Hubert (Experimental and Applied Acarology, 2010)

Bacillus thuringiensis var. tenebrionis control of synanthropic mites (Acari: Acaridida) under laboratory conditions - Tomas Erban; Marta Nesvorna; Michaela Erbanova; Jan Hubert (Experimental and Applied Acarology, 2009)

Combination of the antifeedant bean flour and the predator Cheyletus malaccensis suppresses storage mites under laboratory conditions - Jan Hubert; Stano Pekár (BioControl, 2009)

The return period of wind storms over Europe - Paul M. Della‐Marta; Hubert Mathis; Christoph Frei; Mark A. Liniger; Jan Kleinn; Christof Appenzeller (International Journal of Climatology, 2009)
Accurate assessment of the magnitude and frequency of extreme wind speed is of fundamental importance for many safety, engineering and reinsurance applications. We utilize the spatial and temporal consistency of the European Centre for Medium Range Forecasts ERA‐40 reanalysis data to determine the frequency of extreme winds associated with wind storms over the eastern North Atlantic and Europe. Two parameters are investigated: 10‐m wind gust and 10‐m wind speed. The analysis follows two different view‐points: In a spatially distributed view, wind‐storm statistics are determined individually at each grid‐point. In an integral, more generalized view, the wind‐storm statistics are determined from extreme wind indices (EWI) that summarize storm magnitude and spatial extent. We apply classical peak over threshold (POT) extreme value analysis techniques (EVA) to the EWI and grid‐point wind data. As a reference, a catalogue of the 200 most prominent European storms has been compiled based on available literature. The EWI‐based return periods (RP) estimates of catalogue wind storms range from approximately 0.1 to 300 years, whereas grid‐point‐based RP estimates range from 0.1 to 500+ years. EWIs sensitive to the absolute magnitude of wind speed rank the RP of wind storms in the 1989/1990 and 1999/2000 extended winter season similarly to the RP derived from the distributed approach. The RP estimates derived from EWIs are generally higher when calculated using only land grid‐points compared to RPs derived using whole domain. Both the uncertainties in EWIs and grid‐point‐based RPs show a greater dependence on the wind parameter used than on the uncertainty associated with the EVA for RPs less than 10 years, whereas for RPs greater than 10 years the effect of the different datasets is lower. The EWIs share up to approximately 50% of the variability of the local grid‐point RPs. Copyright © 2008 Royal Meteorological Society

Acaricidal effects of natural six-carbon and nine-carbon aldehydes on stored-product mites - Jan Hubert; Zuzana Münzbergová; Marta Nesvorná; Palmiro Poltronieri; Angelo Santino (Experimental and Applied Acarology, 2008)

Digestive function of lysozyme in synanthropic acaridid mites enables utilization of bacteria as a food source - Tomas Erban; Jan Hubert (Experimental and Applied Acarology, 2008)

Toxicity and efficacy of selected pesticides and new acaricides to stored product mites (Acari: Acaridida) - Jan Hubert; Vaclav Stejskal; Zuzana Munzbergova; Jana Hajslova; Frank H. Arthur (Experimental and Applied Acarology, 2007)

Temperature-dependent population growth of three species of stored product mites (Acari: Acaridida) - Gamila Aspaly; Vaclav Stejskal; Stano Pekár; Jan Hubert (Experimental and Applied Acarology, 2007)

The impact of nitrogen deposition on carbon sequestration in European forests and forest soils - WIM DE VRIES; GERT JAN REINDS; PER GUNDERSEN; HUBERT STERBA (Global Change Biology, 2006)
An estimate of net carbon (C) pool changes and long‐term C sequestration in trees and soils was made at more than 100 intensively monitored forest plots (level II plots) and scaled up to Europe based on data for more than 6000 forested plots in a systematic 16 km × 16 km grid (level I plots). C pool changes in trees at the level II plots were based on repeated forest growth surveys At the level I plots, an estimate of the mean annual C pool changes was derived from stand age and available site quality characteristics. C sequestration, being equal to the long‐term C pool changes accounting for CO 2 emissions because of harvest and forest fires, was assumed 33% of the overall C pool changes by growth. C sequestration in the soil were based on calculated nitrogen (N) retention (N deposition minus net N uptake minus N leaching) rates in soils, multiplied by the C/N ratio of the forest soils, using measured data only (level II plots) or a combination of measurements and model calculations (level I plots). Net C sequestration by forests in Europe (both trees and soil) was estimated at 0.117 Gton yr −1 , with the C sequestration in stem wood being approximately four times as high (0.094 Gton yr −1 ) as the C sequestration in the soil (0.023 Gton yr −1 ). The European average impact of an additional N input on the net C sequestration was estimated at approximately 25 kg C kg −1 N for both tree wood and soil. The contribution of an average additional N deposition on European forests of 2.8 kg ha −1 yr −1 in the period 1960–2000 was estimated at 0.0118 Gton yr −1 , being equal to 10% of the net C sequestration in both trees and soil in that period (0.117 Gton yr −1 ). The C sequestration in trees increased from Northern to Central Europe, whereas the C sequestration in soil was high in Central Europe and low in Northern and Southern Europe. The result of this study implies that the impact of forest management on tree growth is most important in explaining the C pool changes in European forests.

Comparison of Communities of Stored Product Mites in Grain Mass and Grain Residues in the Czech Republic - Jan Hubert; Zuzana Műnzbergová; Zuzana Kučerová; Václav Stejskal (Experimental and Applied Acarology, 2006)

In vitro and in vivo inhibition of α-amylases of stored-product mite Acarus siro - Jan Hubert; Lucie Dolečková-Marešová; Jana Hýblová; Iva Kudlíková; Václav Stejskal; Michael Mareš (Experimental and Applied Acarology, 2005)

No increased risk of non-Hodgkin's lymphoma with steroids, estrogens and psychotropics (Netherlands) - Annette B. Beiderbeck; Elizabeth A. Holly; Miriam C.J.M. Sturkenboom; Jan W. Coebergh; Bruno H.Ch. Stricker; Hubert G.M. Leufkens (Cancer Causes & Control, 2003)

Mites as Selective Fungal Carriers in Stored Grain Habitats - Jan Hubert; Václav Stejskal; Alena Kubátová; Zuzana Munzbergová; Marie Váňová; Eva Žd'árková (Experimental and Applied Acarology, 2003)

Possible association of non-binding of HSP70 to HLA-DRB1 peptide sequences and protection from rheumatoid arthritis - Jan Maier; Markus Haug; Jürgen Föll; Hermann Beck; Hubert Kalbacher; Hans-Georg Rammensee; Günther Dannecker (Immunogenetics, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)